Increased muscular triglyceride content and hyperglycemia in Goto-Kakizaki rat are decreased by egg white hydrolysate. (June 2014) - Ochiai, Masaru; Kuroda, Takashi; Matsuo, Tatsuhiro
Abstract We investigated the fat metabolic characteristics in non-obese and diabetic Goto-Kakizaki (GK) rat and the effects of dietary egg white hydrolysate (EWH) on glucose and fat metabolism. Wistar (W) and GK (G) rats were placed into dietary casein (WC and GC) or EWH (WE and GE) group, and fed their respective diet for six weeks. Triglyceride (TG) content and stearoyl-CoA desaturase (SCD) indices in the soleus muscle were higher in the GC group than WC group in parallel with worsening serum glucose metabolic parameters. The glucose metabolic parameters were significantly improved in the GE group. The TG accumulation and SCD indices in the soleus muscle were also significantly lower in the GE group than in the GC group. In conclusion, dietary EWH not only improved glucose metabolism but also reduced both TG accumulation and SCD indices in the soleus muscle of GK rat.